Post-traumatic OA (PTOA): what have we learned to advance osteoarthritis? - Watt, F (Wolters Kluwer, 2020)
Purpose of review: Current thinking in the study of post-traumatic osteoarthritis (PTOA) is overviewed: the osteoarthritis which follows acute joint injury. The review particularly highlights important publications in the last 18 months, also reflecting on key older literature, in terms of what have we have we learned and have yet to learn from PTOA which can advance the OA field as a whole.